2005
DOI: 10.1080/01421590500047062
|View full text |Cite
|
Sign up to set email alerts
|

Development and reliability testing of TAB a form for 360° assessment of Senior House Officers’ professional behaviour, as specified by the General Medical Council

Abstract: Assessment of the professional behaviour of doctors is increasingly recognized as an essential component of doctors' training (Ben-David et al., 2004) with equally important implications for doctors in permanent posts. TAB is a proforma for such assessment using a 360 degree process in which up to 15 colleagues of a doctor assess that doctor's professional behaviour. The pro forma is presented, together with discussion of the format and approach developed, with particular reference to the General Medical Counc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 7 publications
6
32
0
Order By: Relevance
“…This could be responsible, in part, for the poorer reliability of this MSF seen for GPs. We found that nurses were more reliable in their assessment and this confirms a finding from a previous study in a UK healthcare setting (Whitehouse et al 2005). Perhaps this is because they have the most valid opportunities to observe assessees in practice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could be responsible, in part, for the poorer reliability of this MSF seen for GPs. We found that nurses were more reliable in their assessment and this confirms a finding from a previous study in a UK healthcare setting (Whitehouse et al 2005). Perhaps this is because they have the most valid opportunities to observe assessees in practice.…”
Section: Discussionsupporting
confidence: 89%
“…MSF tools have been widely evaluated for healthcare professionals particularly in North America Wenrich et al 1993;Lipner et al 2002;Lockyer 2003;Lockyer & Violato 2004;Violato et al 2006). In the UK, MSF is increasingly used as evidence in the portfolios of doctors in training and several studies have validated MSFs for this purpose (Thomas et al 1999;Whitehouse et al 2002Whitehouse et al , 2005Davies & Archer 2003;Archer et al 2005;Hesketh et al 2005;Wilkinson & Wade 2005;Davies et al 2008;Wilkinson et al 2008). Small studies have also described using MSF for consultants (Mason et al 2003;Bennett et al 2004) and general practitioners (GP; Griffin et al 2000;Elwyn et al 2005;Murphy et al 2008) and two studies validating a previously developed questionnaire on consultants , and consultants and GPs (Campell et al 2008) have been published.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Mini-PAT is derived from Sheffield peer review assessment tool (SPRAT), a MSF tool originally developed in a paediatric setting but now used in arrange of settings in the UK [6,7]. Other MSF tools are used by some trainees, in particular team assessment of behaviours (TAB) [16]. Mini-PAT includes a self-rating and a facility for free text.…”
Section: Msf-a New and Reliable Methods Evaluation Methods In Specialismentioning
confidence: 99%
“…Based on published research [1][2][3] there are several elements of TAB assessment that must be delivered correctly to optimise validity, and that were listed in the 2010 curriculum. 4 'For each assessment, the foundation doctor should nominate 15 raters.…”
Section: Valid Assessmentmentioning
confidence: 99%